Pengaruh Perkembangan Ojek Online terhadap Peningkatan Ekonomi UMKM di Kecematan Sumbersari, Kabupaten Jember - Graha, Rama Dwi Rendra; Saputra, Fiyoga Bayu; Putra, Dwi Wahyu Maulana (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research explores the impact of the development of online motorcycle taxis on improving the economy of Micro, Small and Medium Enterprises (MSMEs) in the digital era, using Mark Granovetter's Social Network theory. Granovetter emphasized the importance of strong ties and weak ties in supporting economic growth. Strong bonds, such as those between business owners and employees, provide emotional and financial stability. Meanwhile, weak ties, represented by interactions between online motorcycle taxi drivers and customers, open up new market opportunities and increase business visibility. This research uses a case study-based qualitative approach, collecting data through semi-structured interviews and field observations. Interviews were conducted with MSME owners and workers who use online motorcycle taxi services, selected through purposive sampling. Data were analyzed using thematic analysis according to Creswell procedures, including interview transcription, data coding, and identification of main themes. The research results show that collaboration with online motorcycle taxi platforms, such as GoFood, expands market reach and increases MSME sales. In addition, the rating and review system on this platform helps improve service quality and security. Support from strong ties provides stability, while weak ties through online motorcycle taxi platforms create new opportunities and greater visibility. This research emphasizes the importance of synergy between strong ties and weak ties in creating an ecosystem that supports economic growth and social prosperity in the digital era. Thus, technological innovations such as GoFood not only increase operational efficiency but also optimize social relations to achieve larger economic goals.